Electrical forces determine glomerular permeability - Hausmann, Ralf; Kuppe, Christoph; Egger, Herbert; Schweda, Frank; Knecht, Volker; Elger, Marlies; Menzel, Sylvia; Somers, Douglas; Braun, Gerald; Fuss, Astrid; Uhlig, Sandra; Kriz, Wilhelm; et al. (Journal of the American Society of Nephrology, 2010)
There is ongoing controversy about the mechanisms that determine the characteristics of the glomerular filter. Here, we tested whether flow across the glomerular filter generates extracellular electrical potential differences, which could be an important determinant of glomerular filtration. In micropuncture experiments in Necturus maculosus, we measured a potential difference across the glomerular filtration barrier that was proportional to filtration pressure (−0.045 mV/10 cm H2O). The filtration-dependent potential was generated without temporal delay and was negative within Bowman's space. Perfusion with the cationic polymer protamine abolished the potential difference. We propose a mathematical model that considers the relative contributions of diffusion, convection, and electrophoretic effects on the total flux of albumin across the filter. According to this model, potential differences of −0.02 to −0.05 mV can induce electrophoretic effects that significantly influence the glomerular sieving coefficient of albumin. This model of glomerular filtration has the potential to provide a mechanistic theory, based on experimental data, about the filtration characteristics of the glomerular filtration barrier. It provides a unique approach to the microanatomy of the glomerulus, renal autoregulation, and the pathogenesis of proteinuria.